Modelling Customer Satisfaction with Attitudinal Loyalty: Evidence from Indian Telecom Industry - Maheshwari, Prachi; Kushwah, Bharat Singh (International Journal of Psychosocial Rehabilitation, 2020)
Indian telecom companies are under intense competition since the entry of Jio Telecom in Indian Telecom Industry. Telecom operators are under cut throat price competition and operator switching intention of customers is one of the biggest challenge for every operator. The competition has become so stiff among operators that some of the biggest players have gone out of the industry and some of them have merged together to face the competition. Recently 4G has been launched in Indian Telecom Sector and soon sector will witness 5G technology. Intense competition among the Telecom Service provider is visible, in such a scenario maintaining attitudinal loyalty of customer is of immense importance. Present study focuses on role of Service Quality, price perception, brand image and value offer on Customer satisfaction and effect of customer satisfaction on overall customer attitudinal loyalty. For data analysis PLS based structure equation modelling has been used. Different dimension of service quality, price perception, brand image and value offer have been identified. Result of the data analysis revealed that service quality, value offer, and brand image has not depicted positive effect on customer satisfaction while price perception has predicted positive effect on customer satisfaction. Satisfaction has very positive effect on customer loyalty which depicts that in Indian Telecom Sector price perception of customer has very strong role on customer’s satisfaction and so on customer’s attitudinal loyalty.